1972
DOI: 10.4141/cjas72-010
|View full text |Cite
|
Sign up to set email alerts
|

Response of Early Weaned Pigs to Diets of Different Digestible Energy Concentrations and the Effects of Cereal Source and Added Molasses on Performance

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…INTRODUCTION ALTHOUGH dietary energy concentration is known to influence the performance and carcass characteristics of early-weaned pigs (O'Grady and Bowland, 1972;Campbell, Taverner and Mullaney, 1975;O'Grady, 1978) there is little definitive information on the effects of energy intake per se on performance or body composition.…”
mentioning
confidence: 99%
“…INTRODUCTION ALTHOUGH dietary energy concentration is known to influence the performance and carcass characteristics of early-weaned pigs (O'Grady and Bowland, 1972;Campbell, Taverner and Mullaney, 1975;O'Grady, 1978) there is little definitive information on the effects of energy intake per se on performance or body composition.…”
mentioning
confidence: 99%
“…It has been established that pig performance in terms of rate and efficiency of gain, and quality of the carcass, is closely related to the intake of particular nutrients, especially protein and energy (Cooke, Lodge and Lewis, 1972;O'Grady and Bowland, 1972;Fetuga et al, 1975a and b). This study clearly demonstrated that methionine deficiency in the diet of pigs will cause an 'amino acid imbalance' and depression of daily feed consumption, hence a decreased intake of essential nutrients with consequent adverse effects on daily live-weight gain, efficiency of food conversion and quality of the carcass.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the ability of the weanling pig to adjust its feed intake when challenged with diets containing energy levels well below 3400 kcal ME/kg are inconclusive. 0' Grady and Bowland (1972) On an as fed basis, all diets were calculated to contain 20.2% crude protein while the ME content of diets 1, 2, 3 and 4 were 3473, 3279, 3085 and 2890 kcal/kg, respectively ).…”
Section: Trialmentioning
confidence: 99%